Knowledge, Attitude and Practices Regarding Epilepsy among Nurses in a Tertiary Care Hospital in South India - Arvind N. Prabhu, Pai Divya Venkatesh2,Ajo Paul3 , Akhilesh Pandey4, Rajib Mandal5 , Kamath Madhusud (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: In a resource constraint nation like India, nurses play an important role in bridging the epilepsytreatment gap. They are not only caregivers but also opinion leaders. So this study has been undertaken tostudy the knowledge, attitude and practices regarding epilepsy among the nursing staff.Material and Methods: A hospital based cross-sectional study was conducted among 213 staff nurses inSouth India for a period of four months using a 50 item questionnaire.Results: In our study very few nurses (8%) had never witnessed an epileptic seizure .Most of them believedto have insufficient experience in taking care of such patients (86%) and were also reluctant to take careof them (28%). Certain negative beliefs like epileptics are sinners, contagious and under the influence ofsupernatural power were still prevailing among them. They practiced administration of oxygen and givinga metallic object in the hands of the patient during an epileptic seizure. Half of them had average to poorknowledge, attitude and practice regarding epilepsy.Conclusion: The study findings show that knowledge, attitude and practice regarding epilepsy is low.This calls for urgent need to include practical as well as theoritical aspects of epilepsy care in the nursingcurriculum and at the same time address the misconceptions linked to it.